The effectiveness of using intranet in delivering information within Infineon Technologies (M) Sdn Bhd / Shahrul Anuar Mohd Badri (Faculty of Business and Management, 2006)
Many firms today are either planning or implementing corporate intranets. Intranets hold great promise as "organizational Internets" to allow information sharing and collaboration across departments, functions and different information systems within an organization. Yet not much is known about how to implement intranets. In this research, the study is made towards the effectiveness of using intranet in delivering information within Infineon Technologies (M) Soo Bhd. Research objectives for this study are: to identify whether it is effectives to deliver information using intranet in the company, to determine the type of information needed to be display in the intranet, and, to identify the frequency of the employee using intranets as their main information source For the purpose of the study, exploratory research was deployed in order to determine whether it is effective to deliver information using the intranet. Convenience sampling technique has been utilized with 100 respondents or sample size. Self administered questionnaire was used as the survey instrument as the source of primary data. By using the analysis generated by Statistical Package for Social Science (SPSS), results are analyzed and deduction being drawn. The findings from this research paper determine that there are three elements to of effectiveness such as knowledge management, accessibility and, attitude of the employees towards intranet.